2016
DOI: 10.1007/s10354-015-0408-z
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological therapies for Angelman syndrome

Abstract: Angelman syndrome (AS) is a severe neurodevelopmental disorder caused by a loss of the maternally inherited UBE3A; the paternal UBE3A is silenced in neurons by a mechanism involving an antisense transcript (UBE3A-AS). We reviewed the published information on clinical trials that have been completed as well as the publicly available information on ongoing trials of therapies for AS. Attempts at hypermethylating the maternal locus through dietary compounds were ineffective. The results of a clinical trial using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 117 publications
2
8
0
Order By: Relevance
“…Dysregulation of gamma-aminobutyric acid–mediated inhibitory influences on thalamocortical interactions are the likely cause of most sleep problems in AS [ 84 ]. Seizure disorder may exacerbate sleep disturbances [ 84 , 90 ], as may other pathophysiological processes common in AS and not directly related to sleep, such as gastrointestinal discomfort and use of medications for seizures or behaviors [ 91 ]. Another study suggests that the UBE3A gene may be a novel genetic regulator of sleep homeostasis and that dysregulation of the sleep drive may be a key underlying variable in sleep problems in those with AS [ 92 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysregulation of gamma-aminobutyric acid–mediated inhibitory influences on thalamocortical interactions are the likely cause of most sleep problems in AS [ 84 ]. Seizure disorder may exacerbate sleep disturbances [ 84 , 90 ], as may other pathophysiological processes common in AS and not directly related to sleep, such as gastrointestinal discomfort and use of medications for seizures or behaviors [ 91 ]. Another study suggests that the UBE3A gene may be a novel genetic regulator of sleep homeostasis and that dysregulation of the sleep drive may be a key underlying variable in sleep problems in those with AS [ 92 ].…”
Section: Resultsmentioning
confidence: 99%
“…As of this writing, all clinical trials that have attempted to improve outcomes have failed [ 91 ]. Clinical investigations that have been undertaken include those studying dietary supplements aimed at hypermethylating the maternal locus and trials of minocycline and levodopa, all of which showed some effect, but did not lead to significant improvements in neurodevelopment.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer progression can be hindered through systemic knockdown of MALAT1 using antisense oligonucleotide (85,91,201). Antisense-mediated lncRNA targeting has shown to be promising in the treatment of other disorders like Angelman's syndrome through silencing lncRNA UBE3A-AS (268,269). Oncogenic lncRNA H19 is overexpressed in a variety of cancers such as pancreatic tumors.…”
Section: Lncrnas As Biomarkers and In Gene Therapymentioning
confidence: 99%
“…We cannot rule out the possibility that such alternations in AS might be developmentally compensation for the loss of Ube3a. In general, the animal studies can be divided into two groups, one in which Ube3a was reintroduced by direct overexpression and unsilencing the paternal allele, and another where Ube3a substrates and signaling pathways were pharmacologically or genetically normalized (Tan & Bird, ).…”
Section: As Mouse Models Inspired Potential Treatmentsmentioning
confidence: 99%